Pertambangan Emas Tanpa Izin (Peti) di Gampong Pante Ceureumen: Kondisi Sosial, Ekonomi, dan Dampak Lingkungan - Halimah Halimah; Zahra Ferdiana; Viza Mauliza; Yuliana Yuliana; Laila Laila; Agis Purnama; Sopar Sinambela (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze illegal gold mining activities in Gampong Pante Ceureumen and their impacts on the environment and surrounding communities. This research used a qualitative descriptive method through field observations, interviews, and documentation. The results showed that mining activities were carried out in groups consisting of 7–12 workers at each mining site. Each worker had a specific role such as machine operator, gold panner, material transporter, and site supervisor. The mining area was located in mountainous terrain with damaged roads and landslide-prone conditions, causing travel to the site to take up to two days. Workers faced various challenges including machine breakdowns, bad weather, and limited logistics. Food expenses were partially deducted from workers’ salaries, while some workers brought their own food supplies from home such as rice, eggs, instant noodles, onions, and chili. Based on field interviews, there were allegations of weekly payments to certain individuals to maintain mining operations. Illegal mining activities also caused environmental damage including deforestation, landslides, flooding, and disruption of wildlife habitats. The study concludes that illegal gold mining provides short-term economic benefits but creates significant social and environmental risks for the surrounding community.